2007
DOI: 10.1051/futur:20073345
|View full text |Cite
|
Sign up to set email alerts
|

L'empreinte écologique : un indicateur ambigu

Abstract: International audienceCélèbre est devenu le concept d'empreinte écologique qui se présente comme un indicateur composite supposé nous renseigner sur l'espace utilisé par les hommes pour produire les ressources qu'ils utilisent et les déchets qu'ils rejettent, le mettre en regard de la capacité écologique de la planète (la biocapacité), donc le revenu écologique à disposition des hommes. Lorsque l'empreinte écologique excède la biodiversité, cela signifie que la planète est en danger. Le succès de cet indicateu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For comparison, carbon footprints contribute 50-70% of the ecological footprints for the European Union and North America. Nevertheless, the contribution of the carbon footprints, shown in table 1, may still underestimate the true situation based on a recent analysis [12].…”
Section: The Ecological Footprint and Other Environmental Indicators mentioning
confidence: 95%
“…For comparison, carbon footprints contribute 50-70% of the ecological footprints for the European Union and North America. Nevertheless, the contribution of the carbon footprints, shown in table 1, may still underestimate the true situation based on a recent analysis [12].…”
Section: The Ecological Footprint and Other Environmental Indicators mentioning
confidence: 95%
“…Another serious reservation concerns the fact that pollutants and toxic substances are not integrated into the calculation of the EF as well as the issue of biodiversity . Besides, Piguet et al (2007) demonstrated that the global hectare unit cannot correctly account for carbon emissions and therefore must be abandoned. Lastly, the role of technologies is inadequately accounted by the footprint concept.…”
Section: The Ecological Footprint (Or Ef)mentioning
confidence: 98%
“…MFA and PIOT can also integrate a wide range of greenhouse gas emissions but not in a systematic way. For its part, the EF focuses only on carbon dioxide emissions, and this consideration is questionable (Piguet et al, 2007). Suggestions have also been made to include other greenhouse gas emissions .…”
Section: Inventoried Flowsmentioning
confidence: 99%
“…Despite these problems the author still holds that ecological footprint is a relatively good proxy of a countries' sustainability. For a general review of related literature see Wiedmann and Barrett, 2010; for a critical review see van den Bergh and Verbruggen, 1999;Piguet et al, 2007;Venetoulis and Talberth, 2008;Fiala, 2008; for responses to critics see Global Footprint Network, 2007; Kitzes et al, 2009. wellbeing questions used 4 and what kind is not (e.g. the affective dimension or the experienced wellbeing [Kahneman and Krueger, 2006]).…”
Section: Setting Up the Two-dimensional Spacementioning
confidence: 99%